Sparta: History, State and Society - Kulesza, Ryszard (2022)
SHS-Award for the best book in Ancient History in 2022 of the Polish Society for Ancient Studies. Richly illustrated with citations from ancient authors, the book Sparta introduces the reader to the universe of a polis which in the fifth and fourth century BC was a Greek superpower. Part I describes Sparta’s political institutions and mechanisms of governance, the structure of its society, the family, education, lifestyle and, naturally, the organization of the Spartan army and military life. Part II is an outline of the history of Sparta, and Greece, in the two centuries when the polis was at the peak of its influence, extending also into the period of its waning. The book closes with an analysis of ‘imaginary Sparta’ and the ways the Spartan legend has been employed in the shaping of various identities from the early modern era to the present.